Central bank collateral, asset fire sales, regulation and liquidity - Ulrich Bindseil (European Central Bank (ECB), 2013)
This paper analyses the potential roles of bank asset fire sales and recourse to central bank credit to ensure banks' funding liquidity and solvency. Both asset liquidity and central bank haircuts are modelled as power functions within the unit interval. Funding stability is captured as strategic bank run game in pure strategies between depositors. Asset liquidity, the central bank collateral framework and regulation determine jointly the ability of the banking system to deliver maturity transformation and financial stability. The model also explains why banks tend to use the least liquid eligible assets as central bank collateral and why a sudden non-anticipated reduction of asset liquidity, or a tightening of the collateral framework, can destabilize short term liabilities of banks. Finally, the model allows discussing how the collateral framework can be understood, beyond its essential aim to protect the central bank, as financial stability and non-conventional monetary policy instrument.
Keywords: E42; G21; 330; asset liquidity; bank run; central bank collateral framework; liquidity regulation; Unconventional monetary policy